TREN PINJAMAN ONLINE DALAM MILENIAL: TELAAH KONTRIBUTOR INTERNAL DAN EKSTERNAL - Rahmadyanto, Bagus; Ekawaty, Marlina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The rise of loan service providers in the community, supported by shifts in consumption patterns, has succeeded in making people, especially the Millennial Generation, the primary consumers of the business. Known through the P2P lending system, which is often called pay later, it is a means of payment in various buying and selling platforms. However, different factors affect fintech lending usage in each city and community character. This study aims to determine the internal and external factors that affect fintech lending usage by the Millennial Generation in Malang City. This research uses quantitative and exploratory research approaches and questionnaires as research instruments. Through SPSS 26, data were processed using EVA data analysis techniques. The results of this study show three internal factors and two external factors that affect fintech lending usage in 65 respondents of the Millennial Generation in Malang City. This study's results can contribute to filling the research gap and referrals by loan service providers and OJK as a financial supervisor institution.